EKSPERIMENTASI MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) YANG DIMODIFIKASI PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VIII SMP NEGERI SE-KABUPATEN PACITAN TAHUN PELAJARAN 2013/2014 - Budi Sasomo; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: This aim of the research was to know the effect of learning models on mathematics achievement viewed from the student learning independency. The learning model compared were modified GI, GI and direct learning. This research  was a quasi experimental with the factorial design of 3x4. The population of this research was all students class VIII in SMP Negeri in Pacitan regency. The sampling technique used was stratified cluster random sampling. Hypotheses testing was performed using two-way analysis of variance with unequal cells. Based on the results of hypotheses testing, it were concluded that: 1) modified GI learning model give better achievement than GI and direct learning, while GI learning model and direct learning gave the same achievement. 2) Students with independent type have better achievement than students with individualistic type, conscientious type and self-conscious type, students with individualistic type have better achievement than students with conscientious type and self-conscious type, students with conscientious type and self-conscious type have the same achievement. 3) For all of learning independency type, modified GI learning model give better achievement than GI learning model and direct learning, GI learning model and direct learning give the same achievement.  4) For all of learning models,  students with independent type, individualistic type, conscientious type and self-conscious type have the same achievement.Keywords: Modified Group Investigation (GI), student learning independency.